2020
DOI: 10.33086/mhsj.v4i2.1663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the Success Rate of Vesicovaginal Fistula Repair Surgical With Transvaginal and Transabdominal Procedure : Meta Analysis

Abstract: Objective: This paper aims to evaluate the success rate of vesicovaginal fistula (VVF) repair surgery by transvaginal (TVAG) and transabdominal (TPA) procedure. Method: Literatures were searched on the online database, PUBMED and Google Scholar. All of the studies should be belonging on to inclusion criteria. The literatures had qualitative analyze by the authors and bias criteria based on Review Manager 5.3 application. It also had quantitative analyzed by the same application. Results: The literatures have 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
1
Order By: Relevance
“…A study conducted in India by Kumar et al included 58 patients and reported obstructed labor a cause of VVF in 68.96% cases while hysterectomy was cause of fistula in 29.31% cases and success rate of transvaginal route was 84.12% according to their results. 17,18 These results are different from our study where gynecological etiology was main cause of VVF. In our study success rate was 100% in transvaginal repair of fistula.…”
Section: Discussioncontrasting
confidence: 95%
“…A study conducted in India by Kumar et al included 58 patients and reported obstructed labor a cause of VVF in 68.96% cases while hysterectomy was cause of fistula in 29.31% cases and success rate of transvaginal route was 84.12% according to their results. 17,18 These results are different from our study where gynecological etiology was main cause of VVF. In our study success rate was 100% in transvaginal repair of fistula.…”
Section: Discussioncontrasting
confidence: 95%
“…A meta-analysis conducted by Pattinama and Hardianto, involving 25 studies, yielded results consistent with a higher success rate in the abdominal approach than the vaginal approach for vault VVF (Pattinama & Hardianto, 2020). In a separate study by Kumar et al, a transvaginal route was preferred for the repair of simple fistulae.…”
Section: The Route Of Repairs: Vaginal or Abdominal?mentioning
confidence: 88%